The Effect of Work Communication and Employee Competence on Organizational Performance at the Youth and Sports Office - Teguh Wahyono; Riska Anggraini; Kholilul Kholik (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the effect of work communication and employee competence on organizational performance, as reflected in employee performance, at the Youth and Sports Office (Dinas Kepemudaan dan Keolahragaan) of North Sumatra Province. A quantitative associative approach was used with multiple linear regression analysis. The population comprised all 83 civil servants at the office, and a saturated sampling technique was applied so that the entire population served as the research sample. Data were collected through questionnaires and analyzed using classical assumption tests, the t-test, the F-test, and the coefficient of determination with SPSS 25.0. The results show that work communication has a positive and significant partial effect on organizational performance (t = 4.164; sig. = 0.000), and employee competence also has a positive and significant partial effect (t = 5.168; sig. = 0.000) and is the more dominant predictor of the two. Simultaneously, work communication and employee competence significantly affect organizational performance (F = 64.189; sig. = 0.000), explaining 61.6% of its variance (R² = 0.616), while the remaining 38.4% is explained by other factors outside the model. These findings indicate that effective communication and adequate employee competence, when developed together, are key drivers for improving the performance of public sector organizations such as regional youth and sports offices.